2016
DOI: 10.5194/esd-7-797-2016
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting ocean carbon sequestration by direct injection: a global carbon budget perspective

Abstract: Abstract. In this study we look beyond the previously studied effects of oceanic CO2 injections on atmospheric and oceanic reservoirs and also account for carbon cycle and climate feedbacks between the atmosphere and the terrestrial biosphere. Considering these additional feedbacks is important since backfluxes from the terrestrial biosphere to the atmosphere in response to reducing atmospheric CO2 can further offset the targeted reduction. To quantify these dynamics we use an Earth system model of intermediat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 45 publications
1
27
0
Order By: Relevance
“…However, it is not clear whether storage can be accessed fast enough or is appropriately located to meet the mitigation demands for fossil fuels with carbon capture and storage and CDR, so the use of more temporary storage sites has also been investigated. Reith et al [104] recently revisited the idea of using the deep ocean as a site to store carbon from DAC and quantified leakage rates and terrestrial and ocean carbon cycle responses. They found that their targeted atmospheric CO 2 reductions, which were equivalent to the amounts of CO 2 injected, were 16–30% lower on decadal to centennial timescales because of leakage and land and ocean carbon back fluxes that occurred in response to lowering atmospheric CO 2 .…”
Section: Cdr Method-specific Carbon Cycle Responsesmentioning
confidence: 99%
“…However, it is not clear whether storage can be accessed fast enough or is appropriately located to meet the mitigation demands for fossil fuels with carbon capture and storage and CDR, so the use of more temporary storage sites has also been investigated. Reith et al [104] recently revisited the idea of using the deep ocean as a site to store carbon from DAC and quantified leakage rates and terrestrial and ocean carbon cycle responses. They found that their targeted atmospheric CO 2 reductions, which were equivalent to the amounts of CO 2 injected, were 16–30% lower on decadal to centennial timescales because of leakage and land and ocean carbon back fluxes that occurred in response to lowering atmospheric CO 2 .…”
Section: Cdr Method-specific Carbon Cycle Responsesmentioning
confidence: 99%
“…Such open ocean deep convection in the Southern Ocean have been identified in many CMIP5 models (de Lavergne et al, ), the UVic model (Meissner et al, ; Reith et al, ) and also in the Kiel Climate Model, for which the cause could be linked to internal climate variability (Martin et al, ). An important model limitation in this respect is a coarse grid resolution, which for example prevents the correct representation of bottom water formation processes on the continental shelf and thus might favor such events (Bernardello et al, ).…”
Section: Resultsmentioning
confidence: 89%
“…CDR in UVic was simulated by injecting CO 2 at seven separate injections sites, which are located in individual grid boxes near the Bay of Biscay (42.3°N, 16.2°W), New York (36.9°N, 66.6°W), Rio de Janeiro (27.9°S, 37.8°W), San Francisco (31.5°N, 131.4°W), Tokyo (33.3°N, 142.2°E), Jakarta (11.7°S, 102.6°E), and Mumbai (13.5°N, 63°E) (Reith et al, , Figure ). Injections were simulated to be carried out at a 2900 m depth to minimize leakage and maximize retention time.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(e.g., Matthews and Caldeira, 2008;Gillet et al, 2011) occurs in these simulations due to past emissions and climate cycle feedbacks. This committed warming is at some point overlaid by leakage of injected CO 2 out of the ocean (e.g., Orr, 2004;Reith et al, 2016), as well as by oceanic and terrestrial carbon cycle feedbacks that lead to a CO 2 increase in the atmosphere and respective additional warming (see section 3.1). To diagnose the contribution from leakage, we design a leakage-free sensitivity simulation (A1_ Comitw), in which CO 2 emissions are set to zero once the 1.5°C target is reached, and no CO 2 is 160 injected into the deep ocean.…”
mentioning
confidence: 99%